Structure‐Based Design of Selective Noncovalent CDK12 Inhibitors. (26th January 2018) - Johannes, Jeffrey W.; Denz, Christopher R.; Su, Nancy; Wu, Allan; Impastato, Anna C.; Mlynarski, Scott; Varnes, Jeffrey G.; Prince, D. Bryan; Cidado, Justin; Gao, Ning; Haddrick, Malcolm; Jones, Natalie H.; et al.
Abstract: Cyclin‐dependent kinase (CDK) 12 knockdown via siRNA decreases the transcription of DNA‐damage‐response genes and sensitizes BRCA wild‐type cells to poly(ADP‐ribose) polymerase (PARP) inhibition. To recapitulate this effect with a small molecule, we sought a potent, selective CDK12 inhibitor. Crystal structures and modeling informed hybridization between dinaciclib and SR‐3029, resulting in lead compound5 [( S )‐2‐(1‐(6‐(((6, 7‐difluoro‐1 H ‐benzo[ d ]imidazol‐2‐yl)methyl)amino)‐9‐ethyl‐9 H ‐purin‐2‐yl)piperidin‐2‐yl)ethan‐1‐ol]. Further structure‐guided optimization delivered a series of selective CDK12 inhibitors, including compound7 [( S )‐2‐(1‐(6‐(((6, 7‐difluoro‐1 H ‐benzo[ d ]imidazol‐2‐yl)methyl)amino)‐9‐isopropyl‐9 H ‐purin‐2‐yl)piperidin‐2‐yl)ethan‐1‐ol]. Profiling of this compound across CDK9, 7, 2, and 1 at high ATP concentration, single‐point kinase panel screening against 352 targets at 0.1 μm, and proteomics via kinase affinity matrix technology demonstrated the selectivity. This series of compounds inhibits phosphorylation of Ser2 on the C‐terminal repeat domain of RNA polymerase II, consistent with CDK12 inhibition. These selective compounds were also acutely toxic to OV90 as well as THP1 cells. Abstract : Mix and match : Structure‐guided hybridization of dinaciclib (1 ), a potent pan CDK inhibitor, with SR‐3029 (2 ), a compound with weak but selective CDK12 activity, resulted in lead compound7, a highly potent and selective CDK12 inhibitor. The selectivity of compound7 amongst the CDK family and across the kinome is supported by high‐ATP enzyme assays, single‐point kinase panel data, and affinity proteomics using kinase affinity matrix proteomics.